2022
DOI: 10.1111/ejss.13228
|View full text |Cite
|
Sign up to set email alerts
|

Time dependence of hydraulic parameters estimation from transient analysis of mini disc infiltrometer measurements

Abstract: The transient analysis of mini disc infiltrometer (MDI) measurements is an established method for characterising near-surface hydraulic characteristics of soils. The reliability of hydraulic characteristics obtained from transient analysis depends on the (1) adequacy of model, (2) adequacy of data, (3) measurement time and (4) measurement footprint. The measurement time dependence recommendations are reported only for a few soil textures, initially wet samples and tension infiltrometer (TI) with a higher measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
0
0
1
Order By: Relevance
“…Several researchers have also reported that the estimation of the coefficients of Equation ( 6) is affected by the experimental duration, which will also affect the estimation of S and K [21,33]. Latorre et al [6] reported that the DL method is valid only for short to medium times.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have also reported that the estimation of the coefficients of Equation ( 6) is affected by the experimental duration, which will also affect the estimation of S and K [21,33]. Latorre et al [6] reported that the DL method is valid only for short to medium times.…”
Section: Introductionmentioning
confidence: 99%
“…Existem vários métodos de determinação da infiltração de água no solo. Podese utilizar o infiltrômetro de anéis concêntricos (BRANDÃO et al, 2012, MINOSSO et al, 2017, infiltrômetro de MiniDisk (ALAGNA et al, 2019;NAIK;PEKKAT, 2022) e simuladores de chuva (BRANDÃO et al, 2012).…”
Section: Infiltração De áGua No Solounclassified